Characterization of Allergic Polymerized Impurities in Cephalosporins by MALDI-TOF MS/MS Spectrometry - Wang, Dandan; Wang, Jian (Current Pharmaceutical Analysis, 2022)
Background:Characterization of allergic polymerized impurities in cephalosporins is significant to ensure the safety and quality of the products. Objective: The aim of the study was to develop a MALDI-TOF MS/MS method to characterize the structures of polymerized impurities in cefuroxime axetil drug substance and cefetamet pivoxil drug substance. Methods: Calibrant references were TOF mix, including Angiotensin 2, Angiotensin 1, Glu-1- fibrino, N-Acetyl renin, ACTH 1-17, ACTH 18-39, and ACTH 7-38. Matrix was DHB at a concentration of 10 mg·mL-1. Acetone and water were used as solvents to dissolve cefuroxime axetil and cefetamet pivoxil hydrochloride drug substances, respectively. The prepared solutions were mixed with DHB, volatilized to dry, and subjected to MALDI-TOF MS/MS analysis, respectively. MS data were obtained in the linear mode with a power of 80, and MS2 data were obtained in the reflection mode with a power of 120. Molecular weights of polymerized impurities in cefuroxime axetil and cefetamet pivoxil were obtained based on the MS data. Their fragmentation patterns and structural assignments were studied based on the MS2 data. Results: Eight polymerized impurities in cefuroxime axetil drug substance and cefetamet pivoxil hydrochloride drug substance made in China were characterized by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS/MS), among which impurity 133;-133;¤ were in cefuroxime axetil and impurities 133;¥-133;§ were in cefetamet pivoxil. Based on the experimental results, the polymerization mechanism of polymerized impurities in cephalosporins was discussed. Conclusion: MALDI-TOF MS/MS proved to be simple, quick and sensitive for the analysis of polymerized impurities in cephalosporins.
Keywords: pivoxil hydrochloride